Heterologous expression of highly reducing polyketide synthase involved in betaenone biosynthesis. Issue 10 (22nd December 2014) - Ugai, Takahiro; Minami, Atsushi; Fujii, Ryuya; Tanaka, Mizuki; Oguri, Hiroki; Gomi, Katsuya; Oikawa, Hideaki
Abstract : Heterologous expression of highly reducing polyketide synthase and trans -acting enoyl reductase provides insights into the skeletal construction of betaenones. Abstract : A unique highly reducing polyketide synthase (HR-PKS) with a reductase domain was identified in a betaenone biosynthetic gene cluster. Successful heterologous expression and characterization of the HR-PKS and trans -acting enoyl reductase (ER) provide insights into the core structure formation with a decalin scaffold and allow reconstitution of the betaenone biosynthetic machinery.